CO2 capture in integrated steelworks by commercial-ready technologies and SEWGS process. (October 2015) - Gazzani, Matteo; Romano, Matteo C.; Manzolini, Giampaolo
Graphical abstract: Highlights: CO2 capture by SEWGS, MEA and MDEA assessed by process simulations. SEWGS achieves the highest efficiencies (about 37.7%). SEWGS achieves direct CO2 emission reduction from the power block of almost 90%. Significant energy penalties are predicted for MEA cases with high capture rates. MDEA system can approach 90% direct CO2 avoided with 34.6% electric efficiency. Abstract: Integrated steelworks are a significant source of anthropogenic CO2 emissions. In integrated steelworks, which are large stationary plants suitable for application of carbon capture processes, a large fraction of total CO2 is emitted from the power plant, where carbon-rich blast furnace gas (BFG) and other steel mill off-gases are burned to produce electricity by means of a steam cycle or a gas-steam combined cycle. One option to considerably reduce CO2 emission from integrated steelworks without affecting the main iron and steel manufacturing process is hence to apply carbon capture and storage (CCS) technologies on the power plant section either in pre-combustion or in post-combustion configurations. The aim of the present paper is to assess the potential of Sorption Enhanced Water Gas Shift (SEWGS) process for pre-combustion CO2 capture from steel mill off-gas fed to the power plant. The application of the SEWGS process on steel mill off-gas is here investigated and compared to reference monoetanolamine (MEA) and methyldiethanolamine (MDEA) based post-combustion and pre-combustion absorption processes. Different configurations, both for SEWGS and MEA-based cases, have been evaluated and compared from the energy and the environmental point of view. Technical issues associated to the use of the unconventional fuels in state-of-the-art turbines and the effects of steel mill gas blending with natural gas are also discussed. From the mass and energy balances, results show that the MDEA and SEWGS-based plants allow achieving high CO2 capture efficiencies (of the order of 85–90%), while MEA-based plants need a significant additional heat input through natural gas blending to achieve high capture levels. In terms of efficiency and specific primary energy consumption for CO2 avoided (SPECCA), the SEWGS technology with the most advanced sorbent developed allows achieving the highest efficiencies (about 37.7%) and the lowest SPECCA (around 2.2 MJ / kg CO 2 ) among the cases assessed.